The relationship between emotional maturity and aggression among college students - Baquilod, Vanessa M.; Palima, Charivic (2007)
This study was conducted to find whether there is a negative relationship between Emotional Maturity and Aggression Among College Students in Tacloban City and to find out what classification of emotional maturity and aggression do most college students belong. A total number of 135 students from LNU, EVSU and UP were the respondents of the study. They were asked to answer 2 questionnaires to measure emotional maturity and aggression. The data were then correlated using Pearson r Correlation Coefficient and the result yielded to an r of -0.39258199 indicating a moderately low negative relationship between emotional maturity and aggression is accepted. The data also showed that most college students belong to the below average emotional maturity category and moderately aggressive behavior.